Treatment of Acute Proximal Anterior Cruciate Ligament Tears—Part 2: The Role of Internal Bracing on Gap Formation and Stabilization of Repair Techniques. Issue 1 (24th January 2020) - Bachmaier, Samuel; DiFelice, Gregory S.; Sonnery-Cottet, Bertrand; Douoguih, Wiemi A.; Smith, Patrick A.; Pace, Lee J.; Ritter, Daniel; Wijdicks, Coen A.
Background: The latest biomechanical studies on some form of internal bracing have shown improved stabilization for anterior cruciate ligament (ACL) repair, but gap formation and load-sharing function have not yet been reported. Hypothesis: Internal bracing of an adjustable ACL repair construct provides improved stabilization with reduced gap formation and higher residual loading on the ACL. Study Design: Controlled laboratory study. Methods: Internally braced ACL repair constructs with single– and double–cinch loop (CL) cortical buttons, a knotless suture anchor, and a single-CL cortical button with adjustable loop fixation (CLS-ALD) were tested (n = 20 each) in a porcine model at 4 different loads (n = 5 each) over 4000 cycles at 0.75 Hz (n = 80 total). The CLS-ALD technique allowed for additional preconditioning (10 cycles at 0.5 Hz). Test results of the isolated internal brace groups served as a baseline for comparison. Lastly, specimens were pulled to failure (50 mm/min) with a cut internal brace. Final loading and gap formation on the ACL repair construct as well as ultimate strength were analyzed. Results: A statistical significance for peak loads over peak elongation was found between the CLS-ALD and all other reinforced groups (analysis of covariance, P < .001). Accordingly, the adjustable repair technique showed improved load-bearing capability with the internal brace compared with all other fixed repair groups and revealed significantly higher loads than the knotted single-CL group. Also, significantly reduced gap formation was found for the CLS-ALD compared with all other groups ( P < .001), with no gap formation up to 150 N with a final gap of 0.85 ± 0.31 mm at 350 N. A significantly higher ultimate failure load (866.2 ± 104.0 N; P < .001) was found for the button-fixed internal brace group compared with all other groups. Conclusion: Internal bracing had a crucial role in improving the stabilization potential of ACL repair at loads occurring during normal daily activity. The added strength of the internal brace allowed for reducing peak loads on the ACL repair construct as well as restricting gap formation to below 3 mm at loads up to 350 N. Clinical Relevance: Improvements in the mechanical characteristics of current ACL repair techniques that enable reduced gap formation and allow for early range of motion and accelerated rehabilitation may strengthen the self-healing response with the formation of stable scar tissue.